Individual and commercially available antimicrobial coatings for intramedullary nails for the treatment of infected long bone non-unions – a systematic review. (November 2022) - Walter, Nike; Rupp, Markus; Krückel, Jonas; Alt, Volker
Highlights: Treatment of infected long bone non-unions with antimicrobial-coated nails is associated with an overall infect eradication rate of 90.0% and a bone consolidation rate of 85.5% in the literature. Antimicrobial-coated nails are a reasonable treatment option for infected non-unions with minimal side effects. Scientific quality of the publications is low and randomized controlled trials are needed in the future. Abstract: The treatment of infected non-unions of the femur and the tibia remains difficult and requires control of the infection and successful bone healing. Antimicrobial coating of intramedullary nails promises both infection control and stabilization for subsequent bone healing. Both results for custom-made and commercially available antimicrobial coating for intramedullary nails have been published in the past mainly consisting of retrospective case series. The purpose of this work is to review the published literature on techniques and clinical outcome of antimicrobial coatings for intramedullary nails for the treatment of infected long bone non-unions. A systematic literature research in Medline, PubMed, Embase and Cochrane Library was performed in accordance to the PRISMA guidelines. Articles reporting on antimicrobial-coated intramedullary nails for the treatment of infected long bone non-unions were eligible for inclusion. In total, 22 publications were found reporting on 506 infected non-unions of the tibia and femur treated with an antimicrobial-coated nail. Most of them consisted of retrospective case series (72.7%). 469 and 37 patients were treated with an individual antibiotic-loaded PMMA-coating and commercially available gentamicin-coating for intramedullary nails, respectively. The overall infection eradication rate was 90.0% (range 68.7–100%) and the bone consolidation rate was 85.5% (range 57.9–100%). Coating specific side effects were not reported. In conclusion, the treatment of infected long bone non-unions with antimicrobial-coated nails is associated with a high infection control and bone consolidation rate and seems to be a reasonable treatment options with minimal side effects. However, scientific quality of the publications is low and randomized controlled trials are needed.